47.8k views
5 votes
Simplify the variable expression.
14a +(-3a)

User Zarigani
by
6.0k points

2 Answers

3 votes

Answer:

11a

Explanation:

The addition sign does not add the coefficients together. It will already be subtraction with the negative 3a. So, that means the new equation is 14a-3a, then subtracting 14-3 equates to 11.

User To
by
6.5k points
5 votes

Answer:


\huge\boxed{14a+(-3a)=11a}

Explanation:


14a+(-3a)\qquad(+)(-)=(-)(+)=(-)\\\\=14a-3a\qquad\text{combine like terms}\\\\=(14-3)a=11a

User Pbd
by
5.9k points